Capital cultural e território : os nós, os laços e a trama das redes de agricultores familiares do município de Nossa Senhora da Glória - SE - Azevedo, José Franco de (2015)
The study “Cultural Capital and territory: nodes, ties and web of networks of family farmers from Sergipe high hinterland” proposes to analyze the role of cultural capital in solidary reciprocity networks among family farmers for organization and fortification of areas in Nossa Senhora da Glória - SE. The analyzed areas were defined by their historical formation processes, by the reticular and multidimensional relation, power relations, considering the circulation and communication networks, economic processes and mainly the cultural identities. The Cultural Capital is a fundamental key in understanding the territory, specially when it observing the territorial dynamics. The nuclear question is how the cultural capital contributes to the strengthening of the territories and their identity as well the life’s quality of family farmers through close ties, solidarity and trust, contradicting the logic promoted by the state government, which has the new formal social organization patterns reflections, grounded in formal discussions associations, creating new patterns of institutional networks. The theoretical methodological procedures adopted in the study were bibliographic and field research through semi-structured interviews, oral history and direct observation in the establishments, from July 2014 to March 2015. We interviewed leaders of all formal entities (association and labor union) municipal farmers family of Nossa Senhora da Glória - SE, for a total of fifty-six organizations, and the same amount of family farmers associated with these entities, provided that they were not part of the current directorships in order that all answers of farmers leaders and not leaders of the associations were confronted. In conclusion, there is evidence of high levels of cultural capital among family farmers that has contributed to the strengthening of the analyzed territories; however, the state imposition on mandatory formal organization among farmers at certain times appears as an obstacle to the strengthening of capital and consequently the Territories.